Do Variations in Frontal Recess Anatomy Predispose to Mucocele Formation? - Lalee Varghese; Rakesh R. Bright; Aditya V. A. Gunturi; Grace Rebekah; Regi Kurien (International Archives of Otorhinolaryngology)
Introduction Mucoceles are benign expansile cystic lesions commonly seen in the frontoethmoidal region.